Sustainable development and inter-disciplinary trend of research - Sh. M. Aliev; D. N. Nabieva (Юг России: экология, развитие, 2015)
Interdisciplinary direction of scientific research is connected with the solution of the important problems which include integration of scientific knowledge into all spheres of life. A basis of such association are ideas of synergy and information approaches which form methodological base for transition to sustainable development.